Periodic starvation and its effect on growth and muscle composition of Cirrhinus mrigala (Hamilton, 1822) fingerlings: Periodic starvation in C. mrigala - Bhowmik, Tuhin Subhro; Das, Sudhir Kumar; Bhakta, Dibakar (Journal of the Inland Fisheries Society of India, 2023)
The effect of intermittent starvation on the growth and muscle composition of fingerlings of Cirrhinus mrigala was studied. Three treatments were designated as D1, D2, and D3 where fish were starved for one day, two days, and three days in a week, respectively. Each experimental group had three replicates and the experiment was conducted for ten weeks. There was no significant differences in length increment, weight gain, and specific growth rate of fish between the treatment D1 and control though feed consumption was significantly different (P